10z+8z+2=12z+9z+5

Simple and best practice solution for 10z+8z+2=12z+9z+5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 10z+8z+2=12z+9z+5 equation:


Simplifying
10z + 8z + 2 = 12z + 9z + 5

Reorder the terms:
2 + 10z + 8z = 12z + 9z + 5

Combine like terms: 10z + 8z = 18z
2 + 18z = 12z + 9z + 5

Reorder the terms:
2 + 18z = 5 + 12z + 9z

Combine like terms: 12z + 9z = 21z
2 + 18z = 5 + 21z

Solving
2 + 18z = 5 + 21z

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '-21z' to each side of the equation.
2 + 18z + -21z = 5 + 21z + -21z

Combine like terms: 18z + -21z = -3z
2 + -3z = 5 + 21z + -21z

Combine like terms: 21z + -21z = 0
2 + -3z = 5 + 0
2 + -3z = 5

Add '-2' to each side of the equation.
2 + -2 + -3z = 5 + -2

Combine like terms: 2 + -2 = 0
0 + -3z = 5 + -2
-3z = 5 + -2

Combine like terms: 5 + -2 = 3
-3z = 3

Divide each side by '-3'.
z = -1

Simplifying
z = -1

See similar equations:

| -5x^4+36x^2=0 | | 5x^2-5x-2=0 | | x^3-12x^2+36x=0 | | 12x+108=96 | | x^2+10x+21= | | x+18+4x=-11-4x-16 | | .333x+8=x+10 | | x^2-8x-16=23 | | .5x+8=x+10 | | 3x+51= | | x^2=500 | | 43+2x=32 | | 3(3)+5(4)=29 | | 6x-43=3x-10 | | 93+4=[17-(2+3)] | | 4x-7=3.5+x | | 6x^2+15=0 | | 4Y^2+3Y-10=0 | | -18x-30=6 | | 3x+5y=29 | | 82-4x=23x+16 | | 12-7x=111-28x | | -6c+9=-4c-3 | | 6x+5=-79-8x | | 6x^2+37x-35=0 | | -2x=7x-18 | | 2x^2+15=0 | | 4(2c-3)-3(c-4)= | | 80Y^2-210Y-245=0 | | y=-2.5x+4 | | 8=z-5 | | 6x+15=21 |

Equations solver categories